Selective Restriction Of Intra Uterine Growth And Risk Of Perinatal Mortality According To Fetal Sex - Limay-Ríos, Oscar Antonio (2019)
Objectives. To determinate the risk of death in new-boros with diagnosis of Selective intrauterine growth restriction in twin pregnancy according sex. Material and methods. Analytic, cross sectional and retrospective. The sample of new-boms with diagnosis of selective intrauterine growth restriction (SIUGR) was selected in the period between February 21'h, 2011 and November 241', 2014 on the National Maternal Perinatal Institute where were included 60491 new-boros, of which 58629 corresponded to single pregnancies, 1790 to twin pregnancies (683 new-borns with SIUGR; 335 of feminine sex and 348 of masculine sex) and 72 to triple pregnancies.